EDUKASI BAHAYA HIV/AIDS PADA REMAJA DAN MASYARAKAT DI KAMPUNG SANGGARIA KABUPATEN KEEROM - Rohmani Rohmani; Maryorita, Blestina; Felle, Zeth Robert; Guntur Payasan, Lalu Muhammad; Borneo, Hugo Kingson (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2025)
The biggest challenge of today's health problems is still related to the human immunodeficiency virus (HIV) and Acquired Immunodeficiency Syndrome (HIV/AIDS). HIV and AIDS still have a negative stigma in society and are the cause of sufferers, still receiving bad treatment by their families. Every two minutes, one teenage girl or young woman is infected with HIV. In 2021, an estimated 250,000 teenage girls or young women are infected with HIV. The purpose of this community service is for teenagers and the community to recognize early on the signs of people with HIV and AIDS and to stay away from promiscuity which is one of the causes of the increase in HIV and AIDS. The implementation method is carried out by educating teenagers at the high school level aged 15-19 years and the community in Sannggaria Village. The implementation of education is carried out by providing lectures and video presentations explaining early sexual education. The results of the implementation of early sexual education for teenagers showed that 30 teenagers and 20 parents participated in the activity. The results of the knowledge evaluation showed that 90.75% of teenagers understood the material given. There are still teenagers who lack of understanding because in the middle of the process there were obstacles in absorbing information because the teenager had to attend other activities. Conclusion: adolescents' knowledge about HIV and AIDS is good but it needs to be emphasized in families to always supervise their teenagers.